Use of Domestic Polymeric Waste for Surfactant Removal from Wastewater - Thaiara Ramires dos Reis; Donizeti Leonardo Mancini Tolari; Ana Claudia Pedrozo da Silva; Elton Guntendorfer Bonafé; Rafael Block Samulewski; André Luiz Tessaro (Sustainable Chemistry)
This study addresses the environmental challenge of surfactant removal from wastewater, focusing on the increased surfactant use during the COVID-19 pandemic. Polymeric waste, specifically polyurethane (PU) and polyamide (PA), was repurposed for surfactant adsorption to mitigate these environmental impacts. Methods included preparing surfactant solutions of sodium linear alkylbenzene sulfonate (LAS) and dodecyl pyridinium chloride (DPC) and the mechanical processing of polymeric residues. PU and PA were characterized by FTIR-ATR and by the pH at the point of zero charge, which yielded pH = 8.0 for both polymers. The adsorption efficiency was optimized using a central composite face-centered design, varying pH, temperature, and time. The results indicated that PU and PA effectively adsorbed anionic and cationic surfactants, with specific conditions enhancing performance. From the optimized experimental conditions, four assays were carried out to evaluate the adsorption isotherms and kinetics. Among the fitted models, the SIPS model was the most representative, indicating a heterogeneous surface. Regarding LAS, the maximum adsorption capacity values were ~90 and 15 mg g−1, respectively, for PU and PA. Considering the DPC surfactant, lower values were obtained (~36 mg g−1 for PU and 16 mg g−1 for PA). The results are satisfactory because the adsorbents used in this study were second-generation waste and were used without treatment or complex modifications. The study concluded that using polymeric waste for surfactant removal offers a sustainable solution, transforming waste management while addressing environmental contamination. This approach provides a method for reducing surfactant levels in wastewater and adds value to otherwise discarded materials, promoting a circular economy and sustainable waste reuse.